Impact of Various Mulch Materials on Growth, Yield and Quality of Summer Squash (Cucurbita pepo L.) cv. Pusa Alankar - Das, Payel; Rana, D K; Rana, Himani (International Journal of Ecology and Environmental Sciences, 2024)
A field experiment using 5 treatments viz., T1 -Dark blue polythene mulch, T2 - Light blue polythene mulch, T3-Black polythene mulch, T4 -Paddy straw mulch and T5 – control was conducted to investigate the impact of various types of mulch material on growth, yield, and quality of Summer Squash (Cucurbita pepo L.) Cv. Pusa Alankar under the valley conditions of Srinagar Garhwal. The experiment was laid out in a randomised complete block design with five replications. The effect of mulching materials on almost all the growth, yield, and quality parameters under study was found to be statistically significant. The results revealed that the treatment T2 had maximum plant height (81.33 cm) and plant spread (61.12 cm) at harvest. It also showed the maximum collar diameter (1.92 cm) and the minimum days taken for the appearance of the first female flower (30.29 days). Moreover, it exhibited a higher fruit setting percentage of 78.52%, the minimum days taken to the first fruit harvesting (41.28 days) and the maximum number of fruits per plant (7.38), average fruit length (25.26 cm), and yield per plant (3.46 kg). In contrast, the treatment T4 resulted in the maximum plant height at 15 DAT (21.21 cm), average fruit weight (484 g) and fruit diameter (4.68 cm). On the other hand, treatment T1 demonstrated significant effects in terms of plant height at 45 DAT (46.73 cm), plant spread at 30 DAT (32.08 cm), and the number of harvestings (5.05). The experimental findings were diverse, with each treatment showing its influence on different parameters. However, considering the results, the treatment T2 - Light blue polythene mulch appears to be the most suitable option for enhancing the production of summer squash under the valley conditions of Srinagar Garhwal.